(3GdebGdGJ GdSfjI aj eOM NjQ GdHQjIs - (3GdGejQ YKeGf Hf Ydj GdSdWGfjs
(3ChdgG (B:s
(3dg GSJfOJ dYdei Cfg SfO cga efjg hQcf ZjQ egfOe jGSjO GdQSd HOAkG Ke NGJege abJ GdfHjjf ai HOA heNJJe s
(3BNQgG (B:s
(3ef GdebGdI GdJGSYI hGdNeSjf ai eOM HYV aVGFd WGFaI ef Cgd GdHjJ hGdegGLQjf hGdCfUGQ bhdg HYGe CHgi UdGI HGdOhGe Ydi Wg hCUMGHg hGdBd cdge hGdCfHjGA hcd GdQSd ddMce ef BOe ddeMi GdcGed GdgQe s
(3GdeNWhW TYQ ai aVGFd GdQShd hfSHg hSjQJg haVGFd cKjQ ef Gd UMGHI hBd GdHjJs
(3cJHJ Hbde Hg VHWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs